How does the silicon element perform in JD-dyes: a theoretical investigation1. Issue 16 (28th April 2015) - Yang, Li-Na; Chen, Shi-Lu; Li, Ze-Sheng
<x xml:space="preserve">Abstract</x> A dithienosilole-containing silicon-core JD analogue (Y2) displays remarkable light-harvesting capability, favorable thermodynamic properties, good kinetic parameters, and high stability for Y2/(TiO2)38.